High activation and skewed T cell differentiation are associated with low IL-17A levels in a hu-PBL-NSG-SGM3 mouse model of HIV infection. (21st January 2020) - Perdomo-Celis, F; Medina-Moreno, S; Davis, H; Bryant, J; Taborda, N A; Rugeles, M T; Kottilil, S; Zapata, J C
Summary: The humanized NOD/SCID/IL-2 receptor γ-chain null (NSG) mouse model has been widely used for the study of HIV pathogenesis. Here, NSG mice with transgenic expression of human stem cell factor (SCF), granulocyte–macrophage colony-stimulating factor (GM-CSF) and interleukin (IL)-3 (NSG-SGM3) were injected with peripheral blood leukocytes (PBL mice) from two HIV-infected (HIV + ) patients who were under anti-retroviral therapy (ART; referred as HIV + mice) or one HIV-seronegative healthy volunteer (HIV − ). Such mice are either hu-PBL-NSG-SGM3 HIV + or HIV − mice, depending on the source of PBL. The kinetics of HIV replication and T cell responses following engraftment were evaluated in peripheral blood and secondary lymphoid tissues. High HIV replication and low CD4 : CD8 ratios were observed in HIV + mice in the absence of anti-retroviral therapy (ART). Consistent with high activation and skewed differentiation of T cells from the HIV-infected donor, HIV + mice exhibited a higher T cell co-expression of human leukocyte antigen D-related (HLA-DR) and CD38 than HIV − mice, as well as a shifted differentiation to a CCR7 − CD45RA + terminal effector profile, even in the presence of ART. In addition, HIV replication and the activation/differentiation disturbances of T cells were associated with decreased plasma levels of IL-17A. Thus, this hu-PBL-NSG-SGM3 mouse model recapitulates some immune disturbances occurring in HIV-infected patients, underlying its potential use for studying pathogenic events during this infection. Graphical Abstract: